Laser-ablation-based ion source characterization and manipulation for laser-driven ion acceleration. (16th March 2018) - Sommer, P; Metzkes-Ng, J; Brack, F-E; Cowan, T E; Kraft, S D; Obst, L; Rehwald, M; Schlenvoigt, H-P; Schramm, U; Zeil, K
Abstract: For laser-driven ion acceleration from thin foils (∼10 μ m–100 nm) in the target normal sheath acceleration regime, the hydro-carbon contaminant layer at the target surface generally serves as the ion source and hence determines the accelerated ion species, i.e. mainly protons, carbon and oxygen ions. The specific characteristics of the source layer—thickness and relevant lateral extent—as well as its manipulation have both been investigated since the first experiments on laser-driven ion acceleration using a variety of techniques from direct source imaging to knife-edge or mesh imaging. In this publication, we present an experimental study in which laser ablation in two fluence regimes (low: F ∼ 0.6 J cm −2, high: F ∼ 4 J cm −2 ) was applied to characterize and manipulate the hydro-carbon source layer. The high-fluence ablation in combination with a timed laser pulse for particle acceleration allowed for an estimation of the relevant source layer thickness for proton acceleration. Moreover, from these data and independently from the low-fluence regime, the lateral extent of the ion source layer became accessible.